Research: the things we choose fill (Palíndromo, 2017)
Relationship between texts of the book The compass of writing and Marguerite Duras with dissertation Publishing Place, from Vanessa Schutz, related to my research in the master’s in line Contemporaries Artistic Process. Discuss , in a personal way, about my process, artistic interests and how the research is done in me.
Keywords: research; process; publication